A Wafer‐Scale Nanoporous 2D Active Pixel Image Sensor Matrix with High Uniformity, High Sensitivity, and Rapid Switching. Issue 14 (2nd March 2023) - Park, Heekyeong; Sen, Anamika; Kaniselvan, Manasa; AlMutairi, AbdulAziz; Bala, Arindam; Lee, Luke P.; Yoon, Youngki; Kim, Sunkook
Abstract: 2D transition‐metal dichalcogenides (TMDs) have been successfully developed as novel ubiquitous optoelectronics owing to their excellent electrical and optical characteristics. However, active‐matrix image sensors based on TMDs have limitations owing to the difficulty of fabricating large‐area integrated circuitry and achieving high optical sensitivity. Herein, a large‐area uniform, highly sensitive, and robust image sensor matrix with active pixels consisting of nanoporous molybdenum disulfide (MoS2 ) phototransistors and indium–gallium–zinc oxide (IGZO) switching transistors is reported. Large‐area uniform 4‐inch wafer‐scale bilayer MoS2 films are synthesized by radio‐frequency (RF) magnetron sputtering and sulfurization processes and patterned to be a nanoporous structure consisting of an array of periodic nanopores on the MoS2 surface via block copolymer lithography. Edge exposure on the nanoporous bilayer MoS2 induces the formation of subgap states, which promotes a photogating effect to obtain an exceptionally high photoresponsivity of 5.2 × 10 4 A W −1 . A 4‐inch‐wafer‐scale image mapping is successively achieved using this active‐matrix image sensor by controlling the device sensing and switching states. The high‐performance active‐matrix image sensor is state‐of‐the‐art in 2D material‐based integrated circuitry and pixel image sensor applications. Abstract : Ultrasensitive and robust active‐matrix image sensor circuitry is demonstrated by integrating a wafer‐scale nanoporous molybdenum disulfide (MoS2 ) phototransistor array with high‐performance indium‐gallium‐zinc oxide (IGZO) switching transistors. A 4‐inch wafer‐scale 2D)MoS2 is synthesized and a periodic nanopore array is created on its surface to achieve exceptionally high photoresponsivity of 5.2 × 10 4 A W −1 . The device shows a technically advanced form based on large‐area 2D material similar to a commercialized complementary metal–oxide–semiconductor (CMOS) image sensor consisting of a sensor and a driving transistor in the matrix pixel.